2017
DOI: 10.1021/acs.macromol.7b00765
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isocyanate Polyurethane Thermoplastic Elastomer: Amide-Based Chain Extender Yields Enhanced Nanophase Separation and Properties in Polyhydroxyurethane

Abstract: Non-isocyanate polyurethane (NIPU) was synthesized via cyclic carbonate aminolysis using poly(ethylene oxide) (PEO)-and poly(tetramethylene oxide) (PTMO)-based soft segments, divinylbenzene dicyclocarbonate as hard segment, and diamine−diamide (DDA) chain extender. Characterization of the resulting segmented polyhydroxyurethanes (PHUs) reveals that the use of amide-based DDA chain extender leads to unprecedented improvements in nanophase separation and thermal and mechanical properties over segmented PHUs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 74 publications
3
85
0
Order By: Relevance
“…However, most of the non-isocyanate PU systems developed so far do not offer the advantages of rapid reaction at room temperature from liquid, low-viscosity precursors, industrial viability for both small-scale in-field applications and large-scale industrial applications without generating sideproducts, and the ability to form elastomeric materials that have a combination of appropriate elongation and tensile strength [99,103]. While a few non-isocyanate PU elastomers have been reported [94,96,98,99,109,111,113], these new materials have not been fully characterized yet,…”
Section: Non-isocyanate Polyurethanesmentioning
confidence: 99%
“…However, most of the non-isocyanate PU systems developed so far do not offer the advantages of rapid reaction at room temperature from liquid, low-viscosity precursors, industrial viability for both small-scale in-field applications and large-scale industrial applications without generating sideproducts, and the ability to form elastomeric materials that have a combination of appropriate elongation and tensile strength [99,103]. While a few non-isocyanate PU elastomers have been reported [94,96,98,99,109,111,113], these new materials have not been fully characterized yet,…”
Section: Non-isocyanate Polyurethanesmentioning
confidence: 99%
“…Polyurethanes have a high variety of applications including coatings [1], foams [2,3], fibers [4,5,6], adhesives [7], and thermoplastic elastomers [5,8,9]. They are obtained from the reaction of isocyanates and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…When a soft segment with no potential for intersegmental hydrogen bonding is used, such as polybutadiene‐based soft segment, nanophase‐separated PHUs with a much sharper domain interphase like that exhibited by conventional thermoplastic PU elastomer are obtained . Recently, Torkelson et al also reported that incorporating amide‐based, diamine diamide chain extender results in significant improvement in nanophase separation and properties of PHUs . If another method of eliminating intersegmental hydrogen bonding in PHUs is employed, in particular, via functionalization of the hard‐segment hydroxyl group, will well nanophase‐separated PHUs with sharp domain interphases result?…”
Section: Introductionmentioning
confidence: 99%
“…PHU is analogous to PU but possesses an additional hydroxyl group adjacent to every urethane linkage . Although there have been numerous studies on PHU synthesis in recent years, relatively few studies have been focused on segmented, nanophase‐separated PHUs . A significant fraction of conventional PU is segmented copolymer …”
Section: Introductionmentioning
confidence: 99%